2017
DOI: 10.1063/1.4983464
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of persistent magnetoresistance by piezo-strain effect in manganite-based heterostructures

Abstract: Persistent magnetoresistance effects in the phase-separated Pr0.65(Ca0.25Sr0.75)0.35MnO3/SrTiO3 and Pr0.65(Ca0.25Sr0.75)0.35MnO3/0.7PbMg1/3Nb2/3O3–0.3PbTiO3 heterostructures under a low magnetic field are investigated. It is observed that the persistent magnetoresistance effects decrease with increasing temperatures and the values for the heterostructures on 0.7Pb(Mg1/3Nb2/3)O3–0.3PbTiO3 and SrTiO3 substrates are about 86.6% and 33.2% at 40 K, respectively. More interestingly, the applied electric field on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…For centuries, researchers have been devoting their lifetime efforts to making electronics cheaper, more compact, and more energy‐efficient . A good example is that spintronics applications are the minimization of electronic devices . Here, spins, instead of electrons, serve as information storage media, as well as logical and information processing devices.…”
Section: Introductionmentioning
confidence: 99%
“…For centuries, researchers have been devoting their lifetime efforts to making electronics cheaper, more compact, and more energy‐efficient . A good example is that spintronics applications are the minimization of electronic devices . Here, spins, instead of electrons, serve as information storage media, as well as logical and information processing devices.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, manipulating magnetism in semiconductors is the foundation of spintronics. As nonmagnetic materials, hybrid perovskites were recently integrated into spintronic devices and used as a spacer between ferromagnetic (FM) electrodes. It was reported that the magnetic field can assist the preparation of perovskite films, enhancing the performance of PSC . Moreover, the magnetic field effect is significant in perovskites because of the strong spin–orbit coupling (SOC) brought by the heavy atoms (Pb, I) in their building block. , In a recent work, Zhang et al attributed the influence of magnetic field on photoelectric characteristics to the spin-mixing of photogenerated electron–hole pairs with different g -factors .…”
mentioning
confidence: 99%
“…Compared with the traditional electronic computer platforms, spin wave based platforms have significant strengths in size and efficiency . In recent decades, voltage‐driven magnetoelectric (ME) coupling effect, not limited by the requirement of the device size or the conductivity of the control object, has been proved to be a shortcut and energy efficient method . The fundamental voltage tunable phenomena, like control the interplay among the charge, lattice, orbital, and spin degrees of freedom, have also been investigated .…”
Section: Introductionmentioning
confidence: 99%